PERSEPSI ETIKA MAHASISWA AKUNTANSI DAN AUDITOR DALAM SITUASI DILEMA ETIS AKUNTANSI - Rustiana Rustiana (KINERJA, 2006)
The aim of this study is to investigate about perceive differences among accounting students between auditors ethical dilemma in accounting. Two hundred and twenty eight respondents were participated in this research. Ethical perceived are measured by Multidimensional Ethics Scale with tens ethics’ characteristic from 5 constructs. Ethical dilemma in accounting is measured by two hypothetical cases. Data was analysis with independent t-test. These results showed there are differences among accounting students between auditors. The implications of the study are to increasing content of ethic in accounting curricula.Keywords: ethical dilemma, multidimensional ethic scale, accounting student, auditors.